Use the substitution method to solve this system of equations -3x + y = 11                                                                                  ...

Use the substitution method to solve this system of equations

-3x + y = 11                                                                                                   

5x - 2y = -16

Enter answer as an ordered pair using ( )

4 Answers | Add Yours

baxthum8's profile pic

baxthum8 | High School Teacher | (Level 3) Associate Educator

Posted on

Solve the system by using substitution.

`i. )-3x + y = 11`

`ii.) 5x - 2y = -16`

First solve equation i. for y.

`-3x + y = 11`

`y = 3x + 11`

Now substitute the value of y, (3x + 11), for y in the second equation.

`5x - 2y = -16`

`5x - 2(3x + 11) = -16` Solve for x.

`5x - 6x - 22 = -16`

`-x -22 = -16`

`-x = 6` or `x = -6`

Now substitute the value of x, -6, into either of the original equations to find y.

`-3x + y = 11`

` ` `-3(-6) + y = 11`

`18 + y = 11`

`y = -7`

The solution to the system using substitution is (-6, -7).

tonys538's profile pic

tonys538 | Student, Undergraduate | (Level 1) Valedictorian

Posted on

The system of equations -3x + y = 11 and 5x - 2y = -16 has to be solved for x and y.

From -3x + y = 11, x = (y - 11)/3

Substitute this in 5x - 2y = -16

(5*(y - 11))/3 - 2y = -16

5y - 55 - 6y = -48

-y = 7

y = -7

Substitute y = -7 in x = (y - 11)/3

x = (-7 - 11)/3 = -6

The solution of the system of equations is x = -6 and y = -7

wanderista's profile pic

wanderista | Student, Grade 11 | (Level 2) Valedictorian

Posted on

The answer is (-6, -7).

llltkl's profile pic

llltkl | College Teacher | (Level 3) Valedictorian

Posted on

`-3x + y = 11` .................(i)

`5x - 2y = -16` ..................(ii)

From equation (i) we get:

`y=11+3x` ..............(iii)

Now, substituting the value of y in equation (ii) we get:

`5x-2(11+3x)=-16`

`rArr 5x-22-6x=-16`

`rArr -x-22=-16`

`rArr x+22=16`

`rArr x=16-22`

`rArr x=-6`

Putting the value of x in equation (iii) we get:

`y=11+3*(-6)=11-18=-7`

Therefore, by substitution method, the solution for the given system of equations is (-6,-7).

-----------------------------------------------------------------------------

Check:

(i) `-3*(-6)+(-7)=18-7=11`

(ii) `5*(-6)-2*(-7)=-30+14=-16`

Sources:

We’ve answered 318,916 questions. We can answer yours, too.

Ask a question